The pediatric endurance athlete - Solomon, M. L.; Briskin, S.; Sabatina, N.; Steinhoff, J. (Current Sports Medicine Reports, 2017)
Youth sports participation numbers continue to grow in the United States. A shift toward sport specialization has caused an increase in sport training frequency and intensity that places the growing athlete at risk for overtraining, nutritional deficits, and injuries. Individuals who participate in endurance sports are at especially high risk. Youth runners and swimmers are high-risk populations that require special attention to their training schedules, nutritional intake, and injuries. Appropriate scheduling of training, dedicating time to rest, and nutrition education can help prevent problems in the endurance athlete.